Correlation between adiponectin level with common variant (rs9939609) of fat mass and obesity-associated gene in obese type 2 diabetic women - Fatemeh Shool; Alireza Ostadrahimi; Hajie Lotfi; Maryam Abbasi Majdi; Rasoul Mahmoudi; Mehdi Niknam Moghanloo; Farzaneh Ghafarian Alipour; Sadegh Porfaraj; Nosratollah Zarghami (Society of Diabetic Nephropathy Prevention, 2017)
Introduction: It is well-known that there is an association between rs9939609 polymorphism of fat mass and obesity-associated (FTO) gene with obesity in people from different ethnic background. Objectives: This study aimed to assess the association of common polymorphism on adiposity indexes and type 2 diabetic mellitus (T2DM) and its association with adiponectin level in Iranian women. Patients and Methods: A sample population of 83 obese patients was investigated in a study with case-control design. The patients' age, body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), fasting blood sugar (FBS), insulin, insulin resistance, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), glycated hemoglobin, triglycerides (TG) and adiponectin level were measured. The genotype of FTO rs9939609 was considered using specific primers via PCR and sequencing. Results: There was a significant difference between two groups (diabetic and non-diabetic) in terms of their age, FBS, HbA1c, LDL-C, SBP and DBP. The mean ± standard error (SE) of these parameters except for DBP and SBP were higher in diabetic group. The frequency of the TA genotype (48.27%) was higher in the diabetic group. The levels of FBS, HbA1c and insulin resistance index (HOMA-IR) were high in mutant group in comparison with wild group. There was no significant correlation between adiponectin level and anthropometric and metabolic parameters. However, in diabetic patients significant moderate positive correlation was found between HDL-C and adiponectin level (r = 0.473, P = 0.01). Conclusion: The association of rs9939609 FTO polymorphism was significant with FBS, HbA1c, TG, insulin, HOMA and adiponectin level in obese diabetic women who harbored the mutant A allele.